ANALISIS KADAR TIMBAL (Pb) PADA AIR SUMUR GALI DI KAWASAN TEMPAT PEMBUANGAN AKHIR SAMPAH BANJAR SUWUNG BATAN KENDAL DENPASAR SELATAN - Handriyani, Kadek Ayu Tia Surya; Habibah, Nur; Dhyanaputri, I Gusti Ayu Sri (Universitas Pendidikan Ganesha, 2020)
AbstractFinal Waste Disposal Area at Suwung, Denpasar is one of the final waste disposal area that uses an open dumping system for the waste management techniques. These waste management techniques cause the lack of the groundwater quality. On the other hand, this groundwater is still being used as a main water source by the residents around the final waste disposal area. The aim of the study was to determine of the lead concentration in the well water at the Suwung Waste Disposal Area. This research uses descriptive method with observational approach while the analysis of lead was conducted by using atomic absorption spectrophotometry (AAS). Based on the results, it is proved that there is 1 sample contains of the lead concentration more than maximum allowable of lead according to the Minister of Health of Indonesia No. 416/MENKES/PER/IX/1990. The excess of lead concentration in the water samples may influenced by the distance of the dug wells from waste disposal area which does not meet the requirements, so the pollution occur easily.Keywords: Final waste disposal area, lead determination, atomic absorption spectrophotometry (AAS)